DINÂMICA GEOMORFOLÓGICA NO ALTO-MÉDIO RIO MIRANDA - MS - RAFAEL BARTIMANN DE ALMEIDA (2023)
The river landscape is the result of a combination of different factors, and their relationships are never static. Therefore, it is understood that the understanding of geomorphological dynamics is essential to subsidize the environmental management of rivers. The general objective of this thesis was to analyze the geomorphological dynamics and the hydrosedimentological behavior of the upper-middle course of the Miranda River, identifying natural and anthropogenic processes that affect the river in its landscape, considering the different mechanisms related to erosion, transport and sedimentation, responsible for changing the forms and of river processes. To this end, the document is structured in four chapters. In the first two chapters, the research considers the outline of the hydrographic basin, a description of the location and characterization of the study area, and an explanation and evaluation of the river’s morphological characteristics is provided. In the last two chapters, the research focus is on the main channel, the Miranda River, and a hypothesis is made for the compartmentalization of the channel-plain system and characterizes the current hydro-sedimentary regime of the channel, evidence of the type of flow responsible for the morphology of the channel, and the hydraulic geometry relationships. For the development of the thesis, data from satellite images (Landsat-8) and digital elevation models - DEM (Alos-Palsar), organized and processed in a GIS environment (ArcGis), as well as hydro-sedimentological data treated using statistical techniques and other tools (SisCah 1.0 software and Excel). The studied area has a large altitude range and predominantly flat relief associated with plains and plateaus. The highest slopes and altitudes are associated with the Serra da Bodoquena and Serra de Maracajú regions. The drainage pattern is dendritic and the channel structure is 8th order. The Miranda River, the main channel of the basin, is a typical meandering channel, with a sinuosity index of 2.48. Morphometric parameters indicate that the basin has an elongated shape and low drainage capacity, which indicates a strong lithological influence in the region. Based on the degree of confinement of the valley and on their respective geomorphic characteristics, three geomorphological compartments are indicated for the Miranda River. The first compartment contains fluvial features typical of a meandering channel (side bar, central bar, islands). In the second and third compartments, floodplain geomorphic units (meander turns, meander cuts, paleochannels, among others) appear in greater numbers. These geomorphological features provide evidence for a reduction in slope and greater connectivity between channel and plain in high runoff events whose flow exceeds the bankful level. Finally, the hydrological regime of the Miranda River is characterized by high variation in flows, which is related to the dynamics of precipitation and with a different response time between the analyzed fluviometric stations. The flow that shapes the channel in the section of the Bonito station seems to be the maximum flows, while in the Miranda station, the genesis and morphology of the channel seem more related to the effective flow. However, studies of bottom sediments still need to be carried out in order to develop a complete perspective on the channel morphology. Finally, the level of full margins and the presence of geomorphic units typical of plains in the adjacent areas of the third compartment show that the connectivity of the channel-plain system is more frequent in the Miranda station.